Proc. 28th Annual Conference of the International Group for Lean Construction (IGLC) 2020
DOI: 10.24928/2020/0019
|View full text |Cite
|
Sign up to set email alerts
|

Value Stream Map and Visilean® for Prefabricated Concrete Panels Management

Abstract: The lack of process flow planning causes waste of time and material. The value stream map helps workers understanding the flow, identifying waste and planning for the future state. Visilean® helps automate production control. The main objective of this work is to propose a method to improve process flow planning of prefabricated concrete panels based on the application of Value Stream Map and Visilean® to manage the movement of parts in the factory. Results show value stream maps for project, production and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Ioannou and Yang (2016) demonstrated that on-site practitioners may use VSM to observe the daily flow of work in order to evaluate the impact of workflow adjustments. VSM may aid in the detection of possible bottlenecks in the building process, hence contributing to the reduction of waste in the construction industry (Kanai & Fontanini, 2020).…”
Section: Vsm In Construction Industrymentioning
confidence: 99%
“…Ioannou and Yang (2016) demonstrated that on-site practitioners may use VSM to observe the daily flow of work in order to evaluate the impact of workflow adjustments. VSM may aid in the detection of possible bottlenecks in the building process, hence contributing to the reduction of waste in the construction industry (Kanai & Fontanini, 2020).…”
Section: Vsm In Construction Industrymentioning
confidence: 99%
“…In the construction industry, VSMs can help identify the bottlenecks in the construction process and therefore minimize waste (Germano et al 2017, Kanai andFontanini 2020).…”
Section: Value Stream Mappingmentioning
confidence: 99%
“…As stated by Orihuela et al (2015) VSM is a visual tool which permits teams to correctly identify how the flow processes are executing. Additionally, Kanai and Fontanini (2020) pointed out VSM helps to comprehend the flow of material and information. It is a tool that permits to know step by step the entire process of a work.…”
Section: Value Stream Mapping (Vsm)mentioning
confidence: 99%
“…Firstly, Kanai and Fontanini (2020) mentioned three positive factors of the value stream mapping: it helps to visualize the whole process, it is a manner to identify waste. The map is a first step for an implementation.…”
Section: Introductionmentioning
confidence: 99%